Trait and State-Dependent Risk Attitude of Monkeys Measured in a Single-Option Response Task - Fujimoto, Atsushi; Minamimoto, Takafumi (Frontiers in Neuroscience, 2019)
Human and animals show diverse preferences to risks (“trait-like” risk attitude) and shift their preference depending on the state or current needs (“state-dependent” risk attitude). For a better understanding of the neural mechanisms underlying risk-sensitive decisions, useful animal models have been needed. Here we examined the risk attitude of three male monkeys in a single-option response task, in which an instrumental lever-release was required to obtain a chance of reward. In each trial, reward condition, either deterministic (100% of 1, 2, 3, 4 drops of juice) or probabilistic (25, 50, 75, 100% of 4-drop juice) was randomly selected and assigned by a unique visual cue, allowing the monkeys to evaluate the forthcoming reward. The subjective value of the reward was inferred from their performance. Model-based analysis incorporating known economic models revealed non-linear probability distortion in monkeys; unlike previous studies, they showed a simple convex or concave probability distortion curve. The risk preference was stable across sessions, suggesting that our observation reflected the trait-like risk attitude of monkeys. Regardless of the baseline risk preference, all monkeys showed an enhancement of risk preference in a session according to the satiation level (i.e., state-dependent risk attitude). Our results suggest that, without choice or cognitive demand, monkeys show naturalistic risk attitude — diverse and flexible like humans. The current approach may provide a useful animal model of risk-sensitive decisions, facilitating the investigation of the neural mechanisms of decision-making under risk.